2015
DOI: 10.1002/mdc3.12207
|View full text |Cite
|
Sign up to set email alerts
|

More Time with Tremor: The Experience of Essential Tremor Versus Parkinson's Disease Patients

Abstract: Background A broad range of tremors occur in patients with essential tremor and Parkinson's disease; despite this, there are virtually no published data that focus on the patient perspective. The aims were to (1) assess the subjective experience of tremor, comparing essential tremor and Parkinson's disease patients, and (2) assess the clinical correlates of that experience (i.e., what specific clinical characteristics were associated with more experienced tremor)? Methods 121 essential tremor and 100 Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Parkinson's disease-related tremor is a source of significant social anxiety and embarrassment that negatively affects early stage patients' self-image, sense of security, and well-being ( 18 , 19 ). In a survey of 103 PD patients (93.5% Hoehn & Yahr stage I or II), Louis et al found that more than one-quarter agreed with following statements: “My tremor makes me feel negative about myself; I am embarrassed about my tremor; I am depressed because of my tremor; I worry about the future; I am nervous or anxious; I have difficulty concentrating because of my tremor” ( 18 ).…”
Section: Impact Of Tremor For Patients With Early Stage Parkinson's Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkinson's disease-related tremor is a source of significant social anxiety and embarrassment that negatively affects early stage patients' self-image, sense of security, and well-being ( 18 , 19 ). In a survey of 103 PD patients (93.5% Hoehn & Yahr stage I or II), Louis et al found that more than one-quarter agreed with following statements: “My tremor makes me feel negative about myself; I am embarrassed about my tremor; I am depressed because of my tremor; I worry about the future; I am nervous or anxious; I have difficulty concentrating because of my tremor” ( 18 ).…”
Section: Impact Of Tremor For Patients With Early Stage Parkinson's Dmentioning
confidence: 99%
“…In a survey of 103 PD patients (93.5% Hoehn & Yahr stage I or II), Louis et al found that more than one-quarter agreed with following statements: “My tremor makes me feel negative about myself; I am embarrassed about my tremor; I am depressed because of my tremor; I worry about the future; I am nervous or anxious; I have difficulty concentrating because of my tremor” ( 18 ). In a separate survey of 100 PD patients, 36 indicated other people often comment on their tremor ( 19 ). These findings highlight the psychosocial impact tremor can have for patients with early stage PD.…”
Section: Impact Of Tremor For Patients With Early Stage Parkinson's Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral postural tremor of at least 6 Hz was much more frequent in ET patients than in PD patients and represented a typical finding of ET patients in combination with normal echogenicity size of SN. As it was shown by Louis et al, ET patients reported the occurrence of tremor symptoms three times more often than PD patients, which makes this technique especially useful for the evaluation of this population.…”
Section: Discussionmentioning
confidence: 85%
“…The percentage of time with tremor is a valid measure of essential tremor and Parkinson rest tremor severity, 21 and correlates with patient disability. 53 The use of wearable transducers is still an active area of research and development. We do not yet know if continuous recordings of tremor can detect clinical change better than rating scales or transducers used in isolated assessments with prescribed activities.…”
Section: Resultsmentioning
confidence: 99%